Managing New Security Threats in the Caribbean - Chami, Georgina; Teelucksingh, Jerome; Anatol, Marlon (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines non-traditional forms of security and expands the notion of security to include non-state actors and non-human actors. With a wide-ranging look into some of the 'new' security threats facing state and non-state actors today, this book is designed to specifically offer new angles on tackling these threats in the Caribbean region. It explores issues relating to viruses, war and conflict, migration, geopolitics, climate change and terrorism through multi- and interdisciplinary perspectives on global (in-)securities. Each chapter clearly elucidates the connectedness of these non-traditional threats, drawing on a remarkable number of the most recent reports and scholarly works. Most importantly, there is a lack of Caribbean studies in the security themes that are studied. This book is a much needed and timely addition to intellectual thought on Caribbean security in an increasingly fragmented world. It will be of great interest to students of international security studies, human security, global politics, and international relations. Georgina Chami is Lecturer, Institute of International Relations, University of the West Indies, St. Augustine, Trinidad and recipient of the Central America/Caribbean Fulbright Visiting Scholars Program in 2010 Jerome Teelucksingh is Senior Lecturer, in the Faculty of Humanities and Education at The University of the West Indies, St. Augustine Campus, Trinidad. Marlon Anatol is Lecturer at the Open Campus, University of the West Indies, Trinidad.
1.Introduction. By Georgina Chami, Jerome Teelucksingh, and Marlon Anatol -- Part I-The Global Security Landscape -- 2. Multi-Regionalism: Realigning Caribbean Geopolitics for Sustainable Development and Sustainable Security Post-COVID-19. By Anthony J. W. Philipps-Spencer -- 3. China's Diplomatic Forays in the CARICOM-Caribbean Community in the Light of the Belt and Road Initiative. By Nalanda Roy -- Part II - Security Threats in the Caribbean -- 4. Migration, Violent Extremism and Gang Violence: A Case Study of Trinidad and Tobago. By Raghunath Mahabir -- 5. Trafficking in Persons in the CARICOM Region: A Contemporary Perspective. By Marlon Anatol, Sacha Joseph-Mathews, and Amanda Anatol -- Part III - The Intersection of Diplomacy and Security -- 6. Responding to the Covid-19 pandemic: Technology and Tertiary Education. By Brian N. Cockburn, and Georgina Chami -- 7. Health Diplomacy in the CARICOM Region. By Vijay Chattu, Leonard F. Peruski, and Prof. W. Andy Knight -- 8. Threats to Caribbean Energy Security: The Search for Solutions. By Anthony T. Bryan -- Part IV - Future Outlook for Security Management in the Caribbean -- 9. Infirmities of Will: Good Governance, Public Service Reform, and Democratic Legitimacy in the Caribbean. By Christopher Brown -- 10. The Implementation Deficit in CARICOM: An Assessment. By Anthony Gonzales -- 11. Contemporary Security Landscape. By Ivelaw Lloyd Griffith -- 12. Conclusion.
Keywords: Security, International; International Security Studies